Physiological Traits Affecting the Distribution and Wintering Strategy of the Bat Tadarida teniotis ... - Arlettaz, Raphael; Ruchet, Catherine; Aeschimann, John; Brun, Edmond; Genoud, Michel; Vogel, Peter (Zenodo, 2000)
(Uploaded by Plazi for the Bat Literature Project) The ability to enter torpor at low ambient temperature, which enables insectivorous bats to survive seasonal food shortage, is often seen as a prerequisite for colonizing cold environments. Free-tailed bats (Molossidae) show a distribution with a maximum latitudinal extension that appears to be intermediate between truly tropical and temperate-zone bat families. We therefore tested the hypothesis that Tadarida teniotis, the molossid species reaching the highest latitude worldwide (46? N), lacks the extreme physiological adaptations to cold that enable other sympatric bats to enter further into the temperate zone. We studied the metabolism of individuals subjected to various ambient temperatures in the laboratory by respirometry, and we monitored the body temperature of free-ranging individuals in winter and early spring in the Swiss Alps using temperaturesensitive radio-tags. For comparison, metabolic data were obtained from Nyctalus noctula, a typically ...